Annulations of 5-Phenylthiobutenolides and First Synthesis of (±)-Indanostatin - Wang, Shuai; Kraus, George A. (Synlett, 2019)
The first synthesis of indanostatin was achieved in 6 steps. Key steps included a butenolide annulation, oxidation to an indanetrione, and reaction with acetone.
Keywords: 5-phenylthiobutenolides; indanostatin; Hauser–Kraus annulation; hydroquinones; indanedione